Editing Software to Improve the Quality of Students’ Scientific Works: A Systematic Literature Review - Nuphanudin; Nurin Faiza Rahma; Nada Amalina; Marsya Putri Maulidia Aryanti (The Indonesian Institute of Science and Technology Research, 2026)
This systematic literature review examines how academic editing software improves the quality of students’ scientific works and identifies the pedagogical conditions required for responsible use. The review was redesigned to address methodological weaknesses in the previous manuscript, particularly the inconsistency between a claimed literature review and results derived from a single empirical article. Following PRISMA-oriented reporting principles, the review was guided by the question: How does academic editing software contribute to students’ scientific writing quality in higher education? A structured search was conducted across Google Scholar, ERIC, ScienceDirect, SpringerLink, Taylor & Francis Online, and national journal repositories for publications from 2020 to 2025, complemented by selected foundational studies on automated writing evaluation and academic writing technology. Inclusion criteria covered peer-reviewed empirical studies, systematic reviews, conceptual articles, and institutional guidance relevant to automated writing evaluation, reference management, similarity checking, artificial intelligence-assisted writing, digital literacy, and academic integrity in student writing. After screening titles, abstracts, full texts, and relevance to the research question, 32 sources were included for synthesis. The findings were organized into four themes: language accuracy, coherence and argumentation, reference management, and originality. The review shows that tools such as Grammarly, Microsoft Editor, Mendeley, Zotero, Turnitin, and generative AI assistants can support technical accuracy, citation consistency, revision efficiency, and originality awareness. However, the benefits are conditional on digital literacy, ethical judgment, lecturer guidance, and manual revision. Editing software should therefore be positioned as a pedagogical scaffold within academic literacy instruction, not as a substitute for scholarly reasoning, authorship responsibility, or academic integrity.